IMPROVING TEACHERS' ABILITY IN IMPLEMENTING PAKEM THROUGH MGMP AT SMA NEGERI 1 TASIFETO BARAT, NUSA TENGGARA TIMUR - Ulu Emanuel (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to determine whether the supervision activities by supervisors in Subject Teacher Organization (or MGMP) could improve teachers' abilities to implement the active, creative, effective, and fun learning (or PAKEM). To obtain the data needed, this study involved 34 teachers of SMA Negeri 1 Tasifeto Barat and was carried out in three months, starting from 18 August 2019 to 13 October 2019. The results of this study indicated that the teachers’ ability to prepare PAKEM model increased after coaching was carried out by supervisors in the MGMP. The increase was proved by an increase in the average percentage of lesson plan (RPP) preparation, that was 61.19% in cycle I and 67.77% in cycle II as well as the teachers’ ability to compile learning scenarios and components in designing classroom management by determining the types of learning activities that provided opportunities to involve students with detailed and challenging steps for improvement. Therefore, it was suggested that supervisors and school principals took the advantage of the school MGMP forum as a target for teacher training to improve their quality of learning activities and teachers could actively participate in MGMP activities, as one of the forums for improving their quality.